The Contemporary Presidency: Digital Resources to Support Quantitative Scholarship in Presidential Studies. - Deluca, Lisa; Pallitto, Robert (Presidential Studies Quarterly, 2018)
With the increase in digitized content available, new presidential research avails itself to more quantitative analysis. More digitized resources from government agencies and private and university repositories allow presidential scholars access to a broader universe of content. Data for analysis include digitized documents, oral histories, and data sets. Presidential scholars and researchers have the option to collaborate with programmers, computer scientists, and graduate students to become acquainted with current repositories and experiment with new technologies such as text mining and the R programming language.